Reflective Dialogic Assessment: A Narrative Inquiry into Teacher–Student Feedback Journals in Postgraduate ELT Programs - Nurul Maulidiyah Sulham; La Sunra; Muh. Tahir (Lembaga Intelektual Muda (LIM) Maluku, 2026)
In college, feedback is no longer seen as just an evaluation tool, but also as part of the learning process that supports students' active involvement in improving their understanding. However, the practice of feedback is still often one-way, causing students to become passive recipients of lecturers' comments. This research aims to explore how reflective dialogical assessment is constructed through a teacher-student feedback journal and how this practice supports reflective learning in graduate ELT programs. This study uses a qualitative approach with a narrative inquiry design. The participants are graduate students enrolled in the Academic Writing course in the English Language Teaching (ELT) program. Data was collected through teacher-student feedback journals, students' written reflections, and responses to lecturer feedback. Data were analyzed using thematic narrative analysis to identify patterns of reflection, student engagement, and dialogical processes during learning. The findings show that dialogical feedback helps students recognize their academic weaknesses, improve reflection, and become more actively involved in revising their academic writing. Additionally, two-way interaction through feedback journals supports a deeper understanding of the academic writing process. This is shows teacher-student feedback journals have the potential to promote more reflective, dialogical, and student-centered learning practices in the context of postgraduate ELT